CHEST RADIOGRAPHS IN ACUTE PULMONARY EMBOLISM - Zubairi, Ali Bin Sarwar; Husain, Shahid Javed; Irfan, Muhammad; Fatima, Kulsoom; Zubairi, Muhammad Atif; Islam, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Pulmonary embolism (PE) is a serious clinical entity carrying significant morbidity and mortality. Clinically, it is a difficult condition to diagnose and remains under treated condition in Pakistan due to non-availability of objective tests and lack of awareness among physicians. This study was conducted to determine the chest radiographic presentation in known cases of acute PE presenting to a tertiary care hospital. Methods: Hospital records of patients with a diagnosis of acute PE were reviewed from June 2000 until June 2004. Fifty diagnosed cases of acute PE on Spiral Computed tomography (CT) of the chest demonstrating an intraluminal-filling defect were selected. Two chest physicians reviewed the chest radiographs obtained during that hospitalization. In case of discrepancy, a radiologist made final interpretation. Results: The chest radiograph was interpreted as normal in only 18% of patients with acute PE. The most common chest radiographic abnormalities were cardiac enlargement (38%), pulmonary parenchymal infiltrates (34%), atelectasis (26%), pleural effusion (24%), and pulmonary congestion (24%). Other rare findings were elevated hemi diaphragm (14%), pulmonary artery enlargement (14%), and focal oligemia (8%). Conclusions: Cardiomegaly is the most common chest radiographic abnormality associated with acute pulmonary embolism. Chest radiography is not useful in making the diagnosis of acute pulmonary embolism. Its major role is in identification of alternative disease processes that can mimic thrombo-embolism Keywords : Chest radiograph, Echocardiography, Pulmonary embolism